The socio-legal perspectives of child marriage in Zanzibar - Omar Hamdan, Sikujua; Che Soh @ Yusoff, Roslina; Mohd Zin, Najibah; Abdul Hak, Nora (2018)
This paper seeks to discuss the practice of child marriage in Zanzibar community as an existing culture. The custom treats child marriage as one of the accepted forms of marriage in Zanzibar. However, this practice is not in compliance with the international laws. With the change of time, the child marriage has now taken a different shape and treated as “forced marriage”, or is popularly known as “Ndoa za Mkeka” in Zanzibar. The paper examines the reasons and the consequences of forced marriage and its impact on various issues faced by children in Zanzibar such as early pregnancy, school dropouts, poverty and health issues. Although it is against the socio-economic trends according to the international standard, to some extent, this practice of child marriage is still accepted by many as they claim it is not against the Shariah percept. The methodology adopted in this paper is based on the content analysis of reports, leading textbooks, journal articles as well as structured interviews that have been conducted with the relevant people in Zanzibar. It concludes with a series of recommendations and suggestions for improvement in regulating the practice of child marriage in Zanzibar.